2008
DOI: 10.1152/ajpgi.00366.2007
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic prostone activates apical chloride channels in A6 epithelial cells

Abstract: The bicyclic fatty acid lubiprostone (formerly known as SPI-0211) activates two types of anion channels in A6 cells. Both channel types are rarely, if ever, observed in untreated cells. The first channel type was activated at low concentrations of lubiprostone (<100 nM) in >80% of cell-attached patches and had a unit conductance of approximately 3-4 pS. The second channel type required higher concentrations (>100 nM) of lubiprostone to activate, was observed in approximately 30% of patches, and had a unit cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 116 publications
5
79
2
Order By: Relevance
“…Our results with lubiprostone at the whole organ level are consistent with the interpretation of results acquired by others at the cellular level with ClC-2-transfected HEK-293 cells and confluent T84 and A6 cell monolayers (2,16). Lubiprostone opens epithelial Cl Ϫ channels, and this was reflected as stimulation of I sc in our Ussing chamber studies with both small and large intestinal preparations.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results with lubiprostone at the whole organ level are consistent with the interpretation of results acquired by others at the cellular level with ClC-2-transfected HEK-293 cells and confluent T84 and A6 cell monolayers (2,16). Lubiprostone opens epithelial Cl Ϫ channels, and this was reflected as stimulation of I sc in our Ussing chamber studies with both small and large intestinal preparations.…”
Section: Discussionsupporting
confidence: 92%
“…The concentration dependence and EC 50 values in the low nanomolar range for stimulation of I sc by lubiprostone in our study are reminiscent of the results of Bao et al and Cuppoletti et al (2,16), who reported that application of low nanomolar concentrations of lubiprostone to confluent epithelial cell monolayers stimulated electrogenic Cl Ϫ secretion and I sc across the monolayers. Our finding that application of lubiprostone to either the mucosal or submucosal side of the preparations stimulated I sc was unexpected because the ClC-2 channels, on which lubiprostone is believed to act, are reported to be expressed in the apical membrane and should be opened by mucosal but not serosal application.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The ClC-2 channel is known to be activated by a drug, lubiprostone, that is currently used in treatment of constipation (14,15) and by a large variety of fatty acids, including arachidonic acid (13). In ongoing work, we have been searching for the binding region for lubiprostone and other fatty acids.…”
Section: Search For Drug Binding Sitesmentioning
confidence: 99%